Temporomandibular joint disc perforation: a retrospective study - Machon, V; Levorova, J; Hirjak, D; Drahos, M; Foltan, R (International journal of oral and maxillofacial surgery, 2017)
The aim of this study was to evaluate disc perforation diagnosed in patients undergoing arthroscopy of the temporomandibular joint (TMJ). A retrospective analysis of 33 patients with disc perforation (35 joints) was performed. Patients and joints were divided into two groups: those with distal perforation (DP; perforation of the retrodiscal tissue, or the distal area of the disc at the site of ligament insertion into the retrodiscal tissue) and those with central perforation (CP; central and anterior part of the disc). The retrospective evaluation included aetiological factors, clinical symptoms, arthroscopic findings, and the effects of arthroscopic lavage. The most frequent aetiological factors in patients with disc perforation were stress and related parafunctional activities. The most frequent arthroscopic finding in both groups was hyperaemia of the bilaminar zone and synovial tissue. Other predominant arthroscopic findings were the presence of adhesions and anterior disc dislocation in the DP group and synovial hyperplasia in the CP group. Better outcomes of arthroscopic lysis and lavage were found in the CP group than in the DP group. At 12 months after arthroscopic lavage, the results showed that the therapy was satisfactory for 72% of the joints. The most common cause of distal perforation is anterior disc dislocation, whilst chronic inflammatory changes account for central perforation.
Keywords: senioři; léčebná irigace; Temporomandibular Joint Disorders; Retrospective Studies; výsledek terapie; Arthroscopy; discus articularis čelistního kloubu; artroskopie; Middle Aged; mužské pohlaví; Adult; disc perforation; Pain Measurement; Temporomandibular Joint Disc; měření bolesti; ženské pohlaví; retrospektivní studie; Humans; retrospective study; lidé středního věku; temporomandibular joint; dospělí; nemoci temporomandibulárního kloubu; Female; Aged; Therapeutic Irrigation; Treatment Outcome; lidé; Male